Rodinný dům - Qurbonova, Durdona; Durdona Qurbonova (České vysoké učení technické v Praze, 2021)
Předmětem bakalářské práce je zpracování architektonické studie vícegeneračního  rodinného domu včetně vybraných částí z dokumentace pro provedení stavby. Návrh rodinného domu je zadán v obci Jevany. Navržený dům by měl zpříjemnit soužití více generaci a umožnit zlepšení rodinných vázeb. Současně by dům měl zapadat do vesnické krajiny a nerušit její ráz.  K návrhu jsem přistoupila s úctou a respektováním vesnických tradicí a lidských potřeb. Jednoduchost, intimita, život v současnosti a tradice. Z těchto pojmů vy-chází můj návrh.  Jednoduchý dům se sedlovou střechou, která perfektně zapadá do vesnice a uvnitř moderní a dovolující každému z uživatelů mít svůj soukromý prostor a současně zachovat pocit harmonie v rodině

The subject of this bachelor thesis is to elaborate an architectural study of a multigenerational family house, including selected parts from the documentation for the construction. The building plot is located in the village of Jevany. The designed house should be a more pleasant place for co-existence of several generations and help to improve the relationship between family members. At the same time the house should fit into the vllage landscape and not to disturb its character. I started designing with respect for the village traditions and human needs. Simplicity, intimacy, life in the present and traditions. These are what from comes my design. A simple house with a gabled roof that fits perfectly into the village and modern inside,allowing each of the users to have their own private space and at the same time maintain a sense of harmony in the family
Family house
Keywords: Vícegenerační rodinný dům; rodinný dům; rekuperační; tepelné čerpadlo; rodina; terén; stavba; vesnice; venkovský dům; Multigenerational family house; family house; recuperation unit; heat pump; family; plot; construction; village; farm house